How the internal motivation affects the faculty professional development? - analysis based on the SEM - Li Liang; Lee Bih Ni (Global Academic Excellence (M) Sdn Bhd (GAE), 2025)
Based on the perspective of self-determination theory, this study explores the influence mechanism of internal motivation on the faculty professional development, focusing on the three dimensions of identity motivation, social motivation and innovation motivation. Through the establishment of structural equation model (SEM), the empirical analysis of the questionnaire survey of 507 teachers in Guangxi Province, China, found that internal motivation plays an important role in promoting the professional development of teachers. By testing the structural equation model, the standardized path coefficient of identity motivation (IDM) was 0.426, social motivation (SOM) was 0.207, and the path coefficient of innovation motivation (INN) was 0.471, and each path reached high statistical significance (p <0.001). These data not only validate the hypotheses proposed in this study, but also provide strong empirical support for exploring the internal faculty motivation and their impact on professional growth